If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 7) + 6 = 5(x + -6) + -4x + 6 Reorder the terms: 3(7 + x) + 6 = 5(x + -6) + -4x + 6 (7 * 3 + x * 3) + 6 = 5(x + -6) + -4x + 6 (21 + 3x) + 6 = 5(x + -6) + -4x + 6 Reorder the terms: 21 + 6 + 3x = 5(x + -6) + -4x + 6 Combine like terms: 21 + 6 = 27 27 + 3x = 5(x + -6) + -4x + 6 Reorder the terms: 27 + 3x = 5(-6 + x) + -4x + 6 27 + 3x = (-6 * 5 + x * 5) + -4x + 6 27 + 3x = (-30 + 5x) + -4x + 6 Reorder the terms: 27 + 3x = -30 + 6 + 5x + -4x Combine like terms: -30 + 6 = -24 27 + 3x = -24 + 5x + -4x Combine like terms: 5x + -4x = 1x 27 + 3x = -24 + 1x Solving 27 + 3x = -24 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 27 + 3x + -1x = -24 + 1x + -1x Combine like terms: 3x + -1x = 2x 27 + 2x = -24 + 1x + -1x Combine like terms: 1x + -1x = 0 27 + 2x = -24 + 0 27 + 2x = -24 Add '-27' to each side of the equation. 27 + -27 + 2x = -24 + -27 Combine like terms: 27 + -27 = 0 0 + 2x = -24 + -27 2x = -24 + -27 Combine like terms: -24 + -27 = -51 2x = -51 Divide each side by '2'. x = -25.5 Simplifying x = -25.5
| 2m+8=3m-4 | | 5.1-2.4=4x-8.3 | | 6cos(3t)+sin(3t)=0 | | 3b^2-5b-22=0 | | 1.75x+1.25=x+2 | | 28h=24 | | 2m+8=3m | | 0.3r-2.8=3.2-0.2r | | 121b^2+12=156 | | 8.6=2.1-13y | | 2.4-5.1=4x-8.3 | | 4+5y=-21 | | 19.27(s+w)=100 | | 0.33333333333333a=0.33333333333333 | | 9(6+2x)=-(2-4x) | | -4(5-5)+3n= | | -(9x-4)=-5 | | T(9.69+w)=100 | | 120-4(3(-2+3)+5)= | | 2x^2+2y^2-324=0 | | (2x+9)(7x-8)=0 | | 8n^2+4=1156 | | Log(-2a)=log(7-4a) | | 4(x+2)-x=20 | | 9x+6=-6 | | 30x-10=31x | | 5m-3m=1+9 | | 1-4n+6+4=-7n+5 | | 5n+4n=32 | | y-3=-1(x-(-6)) | | 17+7=8x | | 8-h(2h)=72 |